Implementasi Aplikasi Pelayanan Penerbitan Izin Kegiatan Masyarakat oleh Seksi Pelayanan Administrasi : di Ditintelkam Polda Metro Jaya - Ojesa Wileta Panggabean; Ilham Prisgunanto (Prisani Cendekia, 2026)
This study aims to analyze the implementation of the Community Activity Permit Issuance Application as part of public service transformation within the jurisdiction of the Polda Metro Jaya. This policy is a form of implementation of the Regulation of the Indonesian National Police Number 7 of 2023, which promotes the digitalization of licensing services through the SuperApps Presisi Polri. This research employs a qualitative approach with a descriptive-analytical method. Data was collected through interviews, observations, and documentation. The results indicate that the implementation of the application has not been optimal. This is reflected in the low usage rate of the application compared to manual procedures. Several factors influence the implementation, including ineffective policy communication, limitations in resources-particularly from the user side-declining commitment of implementers, and a bureaucratic structure that has not been fully digitally integrated. In addition, there is a gap between the top-down approach used in policy formulation and the needs of the community as service users, who tend to prefer flexibility and direct interaction in the licensing process.